2018
DOI: 10.1016/j.tra.2018.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Transportation policy for high-speed rail competing with airlines

Abstract: This study investigates the desirable transportation policy for a government seeking to regulate the competition between high-speed rail (HSR) and air transportation. To address this issue, we construct a game-theoretic model. A basic assumption underlying the model is that the airline maximizes its own profit whereas the HSR operator maximizes a weighted sum of profit and social welfare due to the government regulation. We assume a two-stage game in which the government sets the weight to maximize social welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…China and Spain accounted for 27% and 13% of the published articles, respectively. Several authors included multiple countries in their analysis [12,41,44,47,63,73,76,101]. In those cases, the articles were mapped to multiple regions.…”
Section: Location Distributionmentioning
confidence: 99%
“…China and Spain accounted for 27% and 13% of the published articles, respectively. Several authors included multiple countries in their analysis [12,41,44,47,63,73,76,101]. In those cases, the articles were mapped to multiple regions.…”
Section: Location Distributionmentioning
confidence: 99%
“…Yonghwa and Hun (2006) [22] The rapid development of HSR had prominent impacts on civil aviation. HSR has had a significant impact on airfares, profits, and social welfare in both the long and short term [6][7][8][9]. For example, after the opening of the Beijing-Shanghai HSR, the civil aviation passenger load factor reduced by 4%, and the ticket price dropped by 15-20%.…”
Section: Hsr and Air Transportmentioning
confidence: 99%
“…A further comparison of the social welfare with and without price discrimination in the airline industry showed that implementing a low-cost strategy in airlines can benefit the social welfare of FSR. Tsunoda (2018) built on the research of Yang and Zhang (2012) and proposed a two-stage model, where the welfare-maximizing government determines the optimal weight on the welfare relative to the FSR's profit (referred to as the degree of regulation in their study) for the FSR operator in the first stage, while the FSA and FSR operators determine their fares in the second stage. They found that the passenger benefits play a crucial role.…”
Section: Social Welfare and Competitionmentioning
confidence: 99%